2014
DOI: 10.1177/1046878114554755
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Engagement

Abstract: The discourse of learner engagement has become prevalent in formal education research and practice in recent years. However, the term has multiple meanings and various constructions, particularly in the context of games and learning, where the coming together of two different disciplinary constructs creates ambiguity and tensions. The notions of 'engagement with education' and 'engagement with games' are not necessarily mutually compatible. This article starts by exploring the use of the term by deconstructing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Most of the literature on play in learning exists within the early childhood setting. However, scholars who write about play at any level of education argue that play-based learning can serve as a vital tool (Barak, 1990;Barnett, 2007;James & Nerantzi, 2019;Sicart, 2014;Swank, 2012;Whitton & Moseley, 2014). Play can create an environment that is conducive to taking risks and experimentation that can lead to creativity and innovation (James & Nerantzi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the literature on play in learning exists within the early childhood setting. However, scholars who write about play at any level of education argue that play-based learning can serve as a vital tool (Barak, 1990;Barnett, 2007;James & Nerantzi, 2019;Sicart, 2014;Swank, 2012;Whitton & Moseley, 2014). Play can create an environment that is conducive to taking risks and experimentation that can lead to creativity and innovation (James & Nerantzi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this, task engagement can be deconstructed into three realisations: 1) behavioural, which can be observed through a) initiation of the task, and b) sustained involvement in the activity, 2) cognitive, which includes concentration, and 3) generally positive emotions. This three strand interpretation has been accepted by the majority of those reporting on task engagement (see for example Chapman, 2003;Jimerson et al, 2003;Fredricks et al, 2004;Appleton, Christenson, Kim, & Reschly, 2006;Lutz, Guthrie, & Davis, 2006;Parsons & Taylor, 2011;Lee, 2012;Marks et al, 2013;Whitton & Moseley, 2014), even though, for various motivations, not all components are always measured (for example Skinner and Belmont (1993) themselves only measured behavioural and emotional engagement).…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the findings of that study, which will be preceded by outlining the theoretical basis for the research undertaken, including a definition of engagement and its measurement, followed by a review of the literature related to engagement utilising technology, and specifically, mobile technology. literature, several authors have concluded that this disparity is because the phrase is employed in reference to two related contexts (see Chapman, 2003, Fredricks et al, 2004Parsons &Taylor, 2011 andWhitton &Moseley, 2014). The first is a more comprehensive usage of the term student engagement referring to the amount of time and efforts students invest in their learning [generally] and other educationally focused activities (National Survey of Student Engagement, 2014), referred to more explicably as school engagement (Fredricks et al, 2004;Jimerson, Campos, & Greif, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the game infringes the principles of positive engagement and motivation in environmental communication (O'Neill & Nicholson-Cole, 2009;Wibeck, 2014), in order to fulfil the aim of the game in this research and communication context. The game hence failed to create a flow, but did present choices and decisions that triggered engagement in line with Whitton and Moseley's (2014) engagement as commitment, referring to the willingness to pay attention, to engage in negotiations, disagreement and dialogue and, as such, contributed to a better understanding of the challenges that lie ahead in order to advance our preparedness to meet climatic changes in Nordic agriculture.…”
Section: Discussionmentioning
confidence: 99%